2016
DOI: 10.1002/hep.28853
|View full text |Cite
|
Sign up to set email alerts
|

Low‐grade endotoxemia and platelet activation in cirrhosis

Abstract: LPS may be responsible for platelet activation and potentially contributes to thrombotic complications occurring in cirrhosis. (Hepatology 2017;65:571-581).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
105
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 33 publications
12
105
0
2
Order By: Relevance
“…In the context of AF, we previously demonstrated that adherence to Med‐diet had several beneficial effects, including a reduction of systemic oxidative stress26 and platelet activation,35 which were in turn associated with a lower rate of MACE. The novel finding of the present study is in the inverse association between adherence to Med‐diet and circulating LPS, which provides a novel insight into the putative anti‐inflammatory effect exerted by Med‐diet 31. It is interesting to note that, among the Med‐diet nutrients, fruits and legumes were those showing a striking association with lower LPS, indicating a relevant role for low‐fat‐content food in modulating circulating LPS 36…”
Section: Discussionsupporting
confidence: 50%
“…In the context of AF, we previously demonstrated that adherence to Med‐diet had several beneficial effects, including a reduction of systemic oxidative stress26 and platelet activation,35 which were in turn associated with a lower rate of MACE. The novel finding of the present study is in the inverse association between adherence to Med‐diet and circulating LPS, which provides a novel insight into the putative anti‐inflammatory effect exerted by Med‐diet 31. It is interesting to note that, among the Med‐diet nutrients, fruits and legumes were those showing a striking association with lower LPS, indicating a relevant role for low‐fat‐content food in modulating circulating LPS 36…”
Section: Discussionsupporting
confidence: 50%
“…However, a recent systematic review and meta‐analysis of anticoagulation in cirrhotic patients with portal vein thrombosis, therapeutic anticoagulation was not associated with major or minor bleeding with some studies even reporting lower rates of spontaneous variceal bleeding . Evidence also suggests that a hypercoagulable state persists in cirrhotic patients with thrombocytopenia, at least in part, due to a process in which lipopolysaccharide‐induced platelet sensitisation results in enhanced in vivo platelet activation . The functional effect of thrombocytopenia in cirrhosis is also influenced by intercurrent illnesses, including sepsis and acute renal impairment, both of which can impact platelet function and are commonly seen in hospitalised patients with decompensated cirrhosis .…”
Section: Discussionmentioning
confidence: 99%
“…Twenty‐four studies reported on 29 statistically significant biomarkers and association with altered IP . Two studies reported that fasting glucose had a weak positive correlation with IP (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies used both zonulin and the dual sugar test and reported a high positive correlation between the two tests ( ρ = 0.891; P = 0.05) (Table ). However, mixed evidence was reported for the strength of association between zonulin and LPS with a weak to moderate positive correlation reported ( ρ = 0.545; P < 0.001); although, one study reported LPS to independently correlate with zonulin levels ( β = 0.002; 95% CI: 0.001, 0.003; P = 0.002) (Table ). The dual sugar test was also reported to have a moderate to high positive correlation with gastroduodenal permeability according to one study ( r = 0.68; P < 0.0001, r = 0.88; P < 0.0001) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation